Description of genetic factors associated with suicidal behavior and suicide: a topical review: Descripción de los factores genéticos asociados a la conducta suicida y suicidio: una revisión de tema | 与自杀行为和自杀相关的遗传因素描述：专题综述 - Constanza-Cañón, Sandra (2024)
Introduction: Suicide and suicidal behaviors (SC) are a complex and multidetermined phenomenon in which different genetic, environmental and individual factors interact. The objective of this study was to carry out a review of the genetic factors associated with suicidal behavior described in the literature of the last 10 years. Methods: A search was made of all available articles, both review articles, case reports and management guidelines under the descriptors in health sciences (DeCS) Suicidal behavior, suicide, depression, exome, genetic markers, genetic variation, human genome, serotonin, norepinephrine, dopamine, computational biology in the databases of Google scholar, LILACS, PubMed and ClinicalKe, official websites such as those of the World Health Organization (WHO) and the Ministry of Health and Social Protection of Colombia were consulted. Development: Genetic studies of CS have been trying for decades to find the "suicide gene", in order to prematurely identify those people with a higher risk of making suicide attempts and prevent them from becoming victims; however, these studies failed to find a gene or group of genes that differentiated between suicidal and nonsuicidal subjects. This type of technology gave rise to genome-wide association studies (GWAS), with which some authors wanted to demonstrate the differences in the genome of patients with suicidal ideas. Conclusions: Knowledge of the genetic factors involved may lead to the possibility of identifying individuals with a higher risk of developing suicidal behavior, thus having better tools and receiving a more mechanistic vision to explore the underlying intermolecular network and prevent deaths from it. cause.